Differential recognition of influenza A virus H1N1 neuraminidase by DNA vaccine-induced antibodies in pigs and ferrets - Tingstedt, Jeanette Linnea; Stephen, Christine; Risinger, Christian; Blixt, Ola; Gunalan, Vithiagaran; Johansen, Isik Somuncu; Fomsgaard, Anders; Polacek, Charlotta; Lassaunière, Ria (Frontiers in Immunology, 2023)
Neuraminidase (NA) accounts for approximately 10-20% of the total glycoproteins on the surface of influenza viruses. It cleaves sialic acids on glycoproteins, which facilitates virus entry into the airways by cleaving heavily glycosylated mucins in mucus and the release of progeny virus from the surface of infected cells. These functions make NA an attractive vaccine target. To inform rational vaccine design, we define the functionality of influenza DNA vaccine-induced NA-specific antibodies relative to antigenic sites in pigs and ferrets challenged with a vaccine-homologous H1N1pdm09 strain. Sera collected pre-vaccination, post-vaccination and post-challenge were analyzed for antibody-mediated inhibition of NA activity using a recombinant H7N1CA09 virus. Vaccine-induced NA-specific antibodies inhibited the enzymatic function of NA in both animal models. Antigenic sites were further identified with linear and conformational peptide microarrays spanning the full NA of H1N1pdm09. The antibodies target critical sites of NA such as the enzymatic site, second sialic binding site and framework residues, shown here by high-resolution epitope mapping. New possible antigenic sites were identified that potentially block the catalytic activity of NA, including an epitope recognized solely in pigs and ferrets with neuraminidase inhibition, which could be a key antigenic site affecting NA function. These findings show that our influenza DNA vaccine candidate induces NA-specific antibodies that target known critical sites, and new potential antigenic sites of NA, inhibiting the catalytic activity of NA.